Medico-legal and ethical aspects of nasal fractures secondary to assault: do we owe a duty of care to advise patients to have a facial x-ray?. Issue 2 (21st November 2012) - Jaberoo, Marie-Claire; Joseph, Jonathan; Korgaonkar, Gillian; Mylvaganam, Kandappu; Adams, Ben; Keene, Malcolm
Abstract : Guidelines advise that x-rays do not contribute to the clinical management of simple nasal fractures. However, in cases of simple nasal fracture secondary to assault, a facial x-ray may provide additional legal evidence should the victim wish to press charges, though there is no published guidance. We examine the ethical and medico-legal issues surrounding this controversial area.